Geo-Electric Parameters, Aquifer Characterization and Groundwater Potential: A case study of Poshiya-Billiri and Environs Northeastern Nigeria - J, Barka; Z. A, Kubbis (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
In view of the importance of water to any growing population, this research work made an attempt to explore the study area for quantitative and qualitative groundwater resources that can meet up with the population growth. Fifteen Vertical Electrical Sounding (VES) locations were investigated using Omega version 2.0 resistivity meter, the field results were analyzed using Win RESIST version 1.0 while Surfer 13 Geosoft and ArcGIS version 10.7.1 softwares were utilized for contouring and map plotting respectively. The interpreted field curves delineated three to four geo-electric stratums with model resistivity and thicknesses varying from 5 to 254.6 Ω-m and 1.4 to 49.1 m respectively and most aquifers were located within the saturated fractured basement and coarse grained sandstone zones. Results of the Dar-Zarrouk analysis to characterize the aquifer system in the study area based on its vulnerability and groundwater yield shows that, the transverse resistance values for the study area ranged from 160.58 to 6375.04 Ω-m2 and the longitudinal conductance values varies from 0.014 to 1.355 Ω-1. The area is therefore interpreted to fall within poor to good protective capacity in terms of vulnerability rating. The hydraulic conductance values which ranged from 3.79 to 58.73 (m/day) and the transmissivity values of 64.17 to 1882.99 m2/day suggested that the area is characterized by moderate to high groundwater yield. It is therefore recommended that areas south of Poshiya, Sansani and west of Komta with high aquifer transmissivity implying high groundwater yield and coincidently having good protective capacity rating should be targeted for drilling of industrial boreholes that can serve the entire community with good and safe groundwater resources.